POTENSI ARANG AKTIF DARI TULANG SAPI SEBAGAI ADSORBEN ION BESI, TEMBAGA, SULFAT DAN SIANIDA DALAM LARUTAN - ', Syamberah; Anita, Sofia; Hanifah, T. Abu (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Chemically the composition of cow bones preparation consist  of 69% of inorganic  phase, 22% of organic phase and 9% water. The organic phase of bone contains 90% collagen. Therefore, the organic phase of cow bone can be used as a source of carbon that functions as  the active charcoal bone. Active charcoal cow  bones made of carbonization and activation process, using activator Na2CO3 with variation concentration of 2.5%; 5% and 7.5%. In this study, the active charcoal cow bones with the variation of concentration are characterizated and obtained the optimum concentration of  Na2CO3  at concentrations of 5% to 7.99% of moisture content, 13,33% of ash content, 27,164 m2/g of methylene blue adsorption and 184, 6947 mg/g of  iod adsorption. The active charcoal  cow bones with Na2CO3 5% was utilized to adsorp ions of iron (SNI 6989-4-2009), copper (SNI 6989-6-2009), sulfate  (SNI 06-2426-1991)  and cyanide  (SNI 6989-76-2011)  in  solution for  24 hours with variations of the concentration of 100, 200, 300, 400, 500 and 600 mg/L. Ions of iron and copper  were  analyzed  using an  Atomic Absorption of Spectrofotometer (AAS), while ions  of sulphate and cyanide analyzed using a Spectrofotometer UV-VIS. The  Optimum adsorption  ability  of  active charcoal  cow bones  is  99,9624%  of the iron ions at a concentration of 300  mg/L, copper ions at 99,6484%  that  obtained at a concentration of 200  mg/L, sulfate ions at 68,274% and 69,594% of cyanide ions at a concentration of 200 mg/L.